Ultrafast Diffraction Switching using GaAs Metasurfaces - Vabishchevich, P. P.; Vaskin, A.; Karl, N.; Reno, J. L.; Sinclair, M. B.; Staude, I.; Brener, Igal (Conference Proceedings - Lasers and Electro-Optics Society Annual Meeting-LEOS, 2020)
We design a resonant metasurface that uses Mie quadrupole modes to suppress the-1 diffraction order. We show that this suppression can be spectrally tuned using optical pumping on a picosecond timescale.
CRIS-Team Scopus Importer:2023-04-20